Frontiers of Solid State Chemistry : Proceedings of the International Symposium on Solid State Chemistry in China. - Feng, S. H. (World Scientific Publishing Company, 2002)
Solid state chemistry is a multidisciplinary field that deals with the synthesis, structural characterization and properties of various solids, and it has been playing a more and more important role in the design and preparation of advanced materials. This book includes the excellent research results recently obtained by a wide spectrum of solid state chemists both from China and from abroad. Among the distinguished contributors are C N R Rao, M Greenblatt and Y T Qian, to name a few. A variety of subjects representing the frontiers of solid state chemistry - which are categorized into solids.